Ruptur Aneurisma Sinus Valsava Ke Ventrikel Kanan: Peranan Ekokardiografi - Primawati A; Krisdinarti L; Mumpuni H (The Indonesian Heart Association, 2016)
1% of the incidence of congenital cardiac anomalies. The most frequent complication is rupture into the right ventricle, causing a shunt from left to right or aortic valve insufficiency with congestive heart failure requiring immediate surgical management. Echocardiography is a diagnostic modality that can be used to help diagnose the presence of sinus Valsalva aneurysm and complications.Clinical case: A 35 years old man with complaints dating dyspnoea on exertion and swelling in both legs. Cardiac auscultation obtained their continuous noisy grade III / VI in the lower left sternal border. Electrocardiography showed sinus tachycardia tachycardia with right axis deviation, right ventricular hypertrophy, and ventricular extrasystoles. Transthoracic echocardiography (TTE) and transesophageal echocardiography (TEE) shows an overview of the sinus of Valsalva aneurysm rupture to the right of the right ventricle.Discussion: When on the clinical findings led to the suspicion rupur sinus of Valsalva aneurysm, the evaluation can be performed using TTE, TEE, Magnetic Resonance Imaging (MRI), maupunkateterisasi heart. Gold standard diagnosis of ruptured sinus Valsalva aneurysm is a cardiac catheterization, but with the advancement of a new generation of engines echocardiography, TTE and TEE has played an important role in the diagnostic confirmation of sinus of Valsalva aneurysm rupture.Conclusion: Echocardiography is the diagnostic modality that is quite helpful in making the diagnosis, complications and surgical therapeutic options in cases of ruptured sinus of Valsalva aneurysm.